Patriotism in Charles Johnson's Middle Passage. Issue 3 (27th May 2017) - Lambert, Raphaël
ABSTRACT: This essay places the issue of patriotism at the heart of Charles Johnson's Middle Passage (1990). The first part looks at the three political systems against which the young protagonist, Rutherford Calhoun, is going to forge his own political beliefs while aboard the slaver the Republic . And the second part argues that Calhoun's unexpected claim toward the end of the story that he is a patriot can be best understood when compared to the decision of the nameless protagonist in Ralph Ellison's Invisible Man (1952) to come out of his hiding place and be a responsible, active citizen. Calhoun and the Invisible Man's belief in the values of equality and tolerance on which the nation was built, as well as their eagerness to play their part to make it work, exemplify, the essay concludes, what political theorists call constitutional patriotism.